2019
DOI: 10.3390/cancers11040502
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ALDH1A1 Inhibitor Targets Cells with Stem Cell Characteristics in Ovarian Cancer

Abstract: A small of population of slow cycling and chemo-resistant cells referred to as cancer stem cells (CSC) have been implicated in cancer recurrence. There is emerging interest in developing targeted therapeutics to eradicate CSCs. Aldehyde-dehydrogenase (ALDH) activity was shown to be a functional marker of CSCs in ovarian cancer (OC). ALDH activity is increased in cells grown as spheres versus monolayer cultures under differentiating conditions and in OC cells after treatment with platinum. Here, we describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 34 publications
4
61
0
Order By: Relevance
“…Given the possibility that CSCs would be more resistant to chemotherapy due to upregulated antiredox mechanisms (11) and considering a recently proposed association between oxidative stress and ferroptosis, a new form of cell death triggered by oxidized lipids, we examined a gene set related to "ferroptosis" (24) in platinum tolerant compared to parental OC cells. Clear differences including upregulated genes involved in glutathione metabolism and anti-oxidant defense mechanisms were observed in platinum-tolerant OC cells vs. chemotherapy-naïve cells (SKOV3,…”
Section: Stemness and Ferroptosis Signatures Are Enriched In Platinummentioning
confidence: 99%
See 2 more Smart Citations
“…Given the possibility that CSCs would be more resistant to chemotherapy due to upregulated antiredox mechanisms (11) and considering a recently proposed association between oxidative stress and ferroptosis, a new form of cell death triggered by oxidized lipids, we examined a gene set related to "ferroptosis" (24) in platinum tolerant compared to parental OC cells. Clear differences including upregulated genes involved in glutathione metabolism and anti-oxidant defense mechanisms were observed in platinum-tolerant OC cells vs. chemotherapy-naïve cells (SKOV3,…”
Section: Stemness and Ferroptosis Signatures Are Enriched In Platinummentioning
confidence: 99%
“…glutathione peroxidase 4 (GPX4) tumor initiation capacity (TIC) (10). Importantly, ovarian CSCs possess a phenotype associated with drug resistance, including enhanced DNA repair, diminished apoptotic responses, increased efflux mechanisms and enhanced antioxidation defense (8,11), which allow them to escape from chemotherapy. The boundaries between stemness and chemotherapy tolerant phenotypes remain blurry and while an overlap exists, it is assumed that distinct pathways drive the two entities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this HTS platform, 64,000 compounds were screened and a potent, highly selective, and novel ALDH1A1 inhibitor CM037 (A37) was identified [111] (Table 2). In OC cells, Matei and Hurley et al demonstrated that CM037 significantly inhibited tumorsphere formation and CSC viability [84]. In a subsequent study by the same group, CM037 treatment promoted DNA damage in OC cells with a corresponding increase in DNA damage response genes.…”
Section: Cm037mentioning
confidence: 96%
“…In OCSCs, of the 19 ALDH isoforms, ALDH1A1 was highly correlated with chemotherapy resistance [78,79,81,82,84,85]. Expression of ALDH1A1 was 100-fold higher in OC cells selected for taxane-resistance in vitro, and ALDH1A1 knockdown sensitized the resistant cells to chemotherapy [82].…”
Section: Aldh and Ovarian Cancermentioning
confidence: 99%